MR imaging of syringohydromyelia and Chiari malformations in myelomeningocele patients with scoliosis. - Samuelsson, L; Bergström, K; Thuomas, K A; Hemmingsson, A; Wallensten, R (American Journal of Neuroradiology, 1987)
The brain and spinal cord were examined with MR imaging in 30 myelomeningocele patients 3-32 years old to study the prevalence of syringohydromyelia and Chiari malformations and to correlate these conditions with developmental scoliosis and spontaneously arrested hydrocephalus. Twelve patients had neurologic deficits above the level of the myelomeningocele and 10 had spontaneously arrested hydrocephalus. MR visualized syringohydromyelia in four patients with widened or focally bulging spinal cords and in eight patients with atrophic spinal cords. All patients had Chiari malformations, 28 of type II and two of type I. Syringohydromyelia was not correlated with type of scoliosis, result of ventriculoperitoneal shunting procedures, radiologic level of the myelomeningocele, or extent of the Chiari malformation. The two patients with the most rapid progression of thoracic scoliosis had the most extensive syringohydromyelia and radiologically low lumbar levels. Neurologic deterioration due to syringohydromyelia and Chiari malformations is probably more common in myelomeningocele than has been recognized previously and may cause developmental scoliosis, loss of ambulation, impaired extremity function, and progressive cranial nerve paralysis.